Accounting for the economic relationship between Japan and the Asian Tigers - Hideaki Hirata; Keisuke Otsu (University of Kent, School of Economics, 2011)
In this paper, we construct a two-country business cycle accounting model in order to investigate quantitatively the relationship between Japan and the Asian Tigers. Our model is based on Backus, Kehoe and Kydland (1994) in which each economy produces tradable intermediate goods that are aggregated to form final goods within each economy. We apply the business cycle accounting method of Chari, Kehoe and McGrattan (2007) and find that the main source of high frequency fluctuation in output in each economy is the fluctuation of production efficiency within its own economy. Furthermore, the growth in the Asian Tigers'production efficiency had a significant positive effect on Japanese economic growth over the 1980-2009 period through the endogenous terms of trade effect.
Keywords: E13; E32; F41; 330; International Business Cycles; Business Cycle Accounting; Terms of trade; Productivity